En kvalitativ studie av sykepleiestudenters opplevelser av nye læringsaktiviteter i kritisk vurdering av kvantitative forskningsartikler - Cecilie Katrine Utheim Grønvik; Signe Gunn Julnes; Atle Ødegård (Septentrio Academic Publishing, 2015)
A qualitative study of nursing students' experience of new learning activities in critical evaluation of quantitative research articles Evidence-Based Practice is a vital part of professional health care and nurses need to have knowledge of research. This article presents nursing students' experience with new learning activities in critical evaluation of quantitative research articles. This experience was studied in focus group interviews with second-year nursing students. The students described it as challenging to understand the various quantitative designs and statistical methods. Specific requirements in the learning activities, constructive feedback, relevance and conformity between learning activities and assessments seem to promote the targeted learning outcome. How students' knowledge and skills are received in practice seems to affect students' attitudes and behavior in relation to the application of research results. To increase evidence-based practice there appears to be a need for innovative processes that can strengthen the cooperation between the nursing education and the field of practice.